Mn / cr co-doped biomimetic coral bone-like kco2(moo4)2(oH)(h2o) electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611285458.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-09
AI Technical Summary
然而,现有掺杂研究大多集中于单一金属离子掺杂或非金属掺杂,对金属离子共掺杂的协同效应缺乏系统探究
[0022]与现有技术相比,本发明具有以下有益效果。
Smart Images

Figure CN122889595A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrochemical energy storage electrode materials technology, specifically to a Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material and its preparation method. Background Technology
[0002] Supercapacitors, as a novel energy storage device situated between traditional capacitors and secondary batteries, have shown broad application prospects in portable electronic devices, hybrid vehicles, and smart grids due to their high power density, rapid charge and discharge capabilities, and excellent cycle stability. However, compared to secondary batteries, supercapacitors have a lower energy density, a bottleneck that severely restricts their promotion and application in large-scale energy storage scenarios.
[0003] Transition metal molybdate materials are considered highly promising pseudocapacitive electrode materials due to their abundant redox active sites and good electrochemical stability. Among them, hydroxyl hydrated potassium cobalt molybdate KCo2(MoO4)2(OH)(H2O) possesses a stable three-dimensional framework network with interlayer K... + Ions act as a support for the interlayer spacing, theoretically effectively buffering volumetric strain during charge-discharge cycles, thereby improving the structural stability of the material. However, this material still faces two major problems in practical applications: first, its intrinsic electronic conductivity is low, resulting in poor charge transport dynamics; second, the lamellar particles are prone to dense stacking, making it difficult for the electrolyte to fully wet the interior of the material, significantly reducing the utilization rate of active sites, and ultimately limiting its capacity and rate performance.
[0004] Currently, modification strategies for molybdate materials mainly include elemental doping, conductive phase compositing, and morphology control. Among these, elemental doping has attracted widespread attention due to its ability to effectively control the band structure, improve intrinsic conductivity, and introduce lattice strain effects. However, existing doping research mostly focuses on single metal ion doping or non-metal doping, lacking systematic exploration of the synergistic effects of metal ion co-doping. In particular, for the specific material system KCo2(MoO4)2(OH)(H2O), no technical solutions have been reported regarding the co-substitution of Co sites by Mn and Cr, and the synergistic control mechanism of Mn / Cr co-doping on lattice anisotropic strain, microstructure evolution, and electrochemical performance remains unclear. Furthermore, although biomimetic hierarchical structures are considered beneficial for electrolyte penetration and ion transport, the fabrication process for directionally constructing a biomimetic coral-like three-dimensional framework in this material system remains a gap.
[0005] In summary, developing a KCo2(MoO4)2(OH)(H2O) electrode material with a Mn / Cr co-doped synergistically controlled lattice structure and a biomimetic coral bone-like multi-level morphology is of significant research importance and application value for improving the energy density and power density of supercapacitors. Summary of the Invention
[0006] In a first aspect, this invention provides a Mn / Cr co-doped biomimetic coral skeleton-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material. The electrode material is grown in situ on a nickel foam substrate, and the active material is Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O). Mn and Cr ions are dissolved into the crystal lattice by substituting Co sites, inducing anisotropic lattice expansion without disrupting the parent KCo2(MoO4)2(OH)(H2O) main crystal phase framework. The lattice expansion along the a-axis is greater than that along the b- and c-axis. The microstructure of the electrode material is a three-dimensional biomimetic coral skeleton multi-level porous structure formed by the self-assembly of ultrathin nanosheets. Mn is used in the form of Mn... 3+ / Mn 4+ Cr exists in mixed valence states, with Cr mainly existing as Cr 3+ Valence states exist, with a small amount being Cr. 6+ The MoO4 tetrahedral rigid framework within the crystal lattice remains intact, and the Mo element retains its +6 valence. The 5% Cr-doped sample of this invention achieves an areal capacitance of 18.88 F / cm² at a current density of 0.001 A / cm². 2 This invention utilizes the synergistic effect of co-doping-induced anisotropic lattice expansion and biomimetic coral bone hierarchical pore structure to improve ion transport dynamics, increase redox active sites, and solve the problems of poor conductivity and low utilization of active sites in traditional molybdates. It can be used as a supercapacitor electrode.
[0007] Furthermore, the electrode material satisfies at least one of the following characteristics:
[0008] (1) When forming the biomimetic coral bone multi-level skeleton structure, the Mn / Co atomic ratio is 1.0, and the oxygen content is close to the theoretical stoichiometric ratio of KCo2(MoO4)2(OH)(H2O);
[0009] (2) The molar percentage of Cr doping is 1%~7%;
[0010] (3) The XRD phase of the electrode material matches the standard card 04-015-9088, with no impurity phase diffraction peaks; the anisotropy of the cell parameters increases, with the expansion amplitude of the a-axis being 1.70%, the expansion amplitude of the b-axis being 1.06%, and the expansion amplitude of the c-axis being 0.43%.
[0011] Preferably, when the Cr doping molar percentage is 3%, the electrode exhibits the lowest charge transfer impedance; when the Cr doping molar percentage is 5%, the electrode areal capacitance reaches 18.88 F / cm² at a current density of 0.001 A / cm². 2 When the Cr doping molar percentage is 7%, the ion transport channels are further widened, and the electrode has the best rate retention capability.
[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned Mn / Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material, comprising the following steps:
[0013] The first step is to dissolve cobalt nitrate hexahydrate and potassium permanganate in deionized water and stir magnetically to obtain a homogeneous metal salt solution.
[0014] The second step is to add ammonium heptamolybdate tetrahydrate, potassium dichromate and ammonium fluoride in sequence, and stir continuously to obtain a mixed precursor solution.
[0015] The third step involves transferring the obtained mixed precursor solution into a polytetrafluoroethylene-lined high-pressure reactor, placing nickel foam as an in-situ growth substrate, sealing it, and then carrying out a hydrothermal reaction. After the hydrothermal reaction is completed, the reactor is allowed to cool naturally to room temperature. The active precursor and the nickel foam substrate are then removed, washed, and dried.
[0016] The fourth step involves placing the dried active precursor and the nickel foam substrate in a muffle furnace for programmed heating and calcination. After calcination, the temperature is then programmed to decrease, and the furnace is cooled to room temperature to obtain the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material in situ loaded on the nickel foam substrate.
[0017] Preferably, in the first step, the amount of cobalt nitrate hexahydrate added is 3 mmol, the amount of potassium permanganate added is 1 mmol, and the volume of deionized water is 60 mL; in the second step, the amount of ammonium fluoride added is 12 mmol, and the total amount of ammonium heptamolybdate tetrahydrate and potassium dichromate is fixed at 4 mmol; the mixture is stirred for 30 min to fully dissolve the cobalt salt and potassium permanganate, and then the molybdenum source, chromium source, and ammonium fluoride are added, followed by stirring for another 30 min to ensure thorough mixing of all components. By adjusting the amount of potassium dichromate added, the molar percentage of Cr doping in the system is controlled to be 1%~7%.
[0018] Preferably, in the third step, the hydrothermal reactor has a capacity of 100 ml, and the nickel foam has a capacity of 1 cm × 1 cm × 0.15 cm; the hydrothermal reaction temperature is 140 ℃, and the holding time is 8 h; the washing is performed with deionized water three times; the drying temperature is 80 ℃, and the drying time is 1 h.
[0019] Preferably, in the fourth step, the calcination process involves heating to 300°C over 2 hours, holding the temperature for 3 hours, then cooling down to below 200°C over a 2-hour program, and finally cooling to room temperature with the furnace.
[0020] In a third aspect, the present invention provides the application of the above-mentioned Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material or the electrode material prepared by the above preparation method in a supercapacitor, wherein the electrolyte is a 3 mol / L KOH alkaline electrolyte, and the supercapacitor is a three-electrode testing device or an asymmetric supercapacitor device.
[0021] Beneficial effects of the invention
[0022] Compared with the prior art, the present invention has the following beneficial effects.
[0023] First, this invention employs a Mn / Cr co-doping strategy. Mn and Cr ions are dissolved into the KCo2(MoO4)2(OH)(H2O) lattice by substituting Co sites. This induces anisotropic lattice expansion, with the a-axis, which has the lowest atomic packing density, preferentially undergoing lattice expansion. This effectively widens the ion transport channels within the crystal, reduces the ion migration barrier, and significantly improves the rate performance of the electrode material. Furthermore, the high-valence Mn... 3+ / Mn 4+ and Cr 3+ The introduction of Co can induce partial Co within the lattice 2+ Converted to Co 3+ This increases the density of active sites for redox couples, thereby enhancing the pseudocapacitive energy storage capacity. Simultaneously, Mn / Cr co-doping does not disrupt the bonding environment of the rigid tetrahedral MoO4 framework in the parent KCo2(MoO4)2(OH)(H2O), ensuring the long-range order and cycle stability of the main structure.
[0024] Secondly, this invention, through precise control of the precursor formulation, can directionally obtain a three-dimensional biomimetic coral-like hierarchical porous structure formed by the self-assembly of ultrathin nanosheets. This structure possesses a biomimetic porous structure, significantly increasing the specific surface area of the material, which is beneficial for the full wetting and rapid penetration of the electrolyte, allowing deep active sites to be exposed and utilized. The ultrathin nanosheets shorten the solid-phase ion diffusion distance, accelerating the Faraday reaction kinetics. The dense rod-shaped core acts as a mechanical support framework, effectively suppressing structural collapse and peeling of the nanosheet layers during long-term charge-discharge cycles. The hierarchical structure of core support and shell activation achieves a balance between structural mechanical stability and electrochemical activity.
[0025] Third, this invention employs an in-situ hydrothermal growth combined with high-temperature calcination process, allowing the active material to nucleate and grow directly on the surface of the nickel foam substrate. This avoids the use of binders and conductive agents in traditional coating processes, simplifying the electrode preparation process. Simultaneously, it achieves close interfacial contact between the active material and the current collector, significantly reducing contact resistance and interfacial charge transfer impedance, which is beneficial for the rapid transport of electrons between the current collector and the active material. The process parameters for each step are clearly defined and controllable, the operation is simple, and it possesses good batch repeatability and scalability potential.
[0026] Fourth, the Mn / Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) electrode material prepared by this invention exhibits the lowest charge transfer impedance when the Cr doping molar percentage is 3%; and at a Cr doping molar percentage of 5%, it achieves a resistance of 0.001 A / cm. 2 At current densities, the area specific capacitance can reach 18.88 F / cm². 2 When the Cr doping molar percentage is 7%, the electrode exhibits the best rate retention capability. This indicates that by adjusting the Cr doping ratio, capacity, rate capability, and impedance can be controlled as needed to meet the performance requirements of different application scenarios.
[0027] This invention provides experimental basis and theoretical reference for the doping modification and biomimetic morphology construction of molybdate-based electrode materials. The prepared electrode materials have broad application prospects in supercapacitor devices in portable electronic devices, hybrid vehicles and smart grid energy storage. Attached Figure Description
[0028] Figure 1 The image shows the XRD pattern of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of this invention.
[0029] Figure 2 This is a crystal structure diagram of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of the present invention;
[0030] Figure 3 This is a SEM image of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of the present invention;
[0031] Figure 4 This is the EDS image of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of the present invention;
[0032] Figure 5The image shows the elemental distribution of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of this invention; wherein: (a) is the distribution of K; (b) is the distribution of Co; (c) is the distribution of Mo; (d) is the distribution of O; (e) is the distribution of Mn; and (f) is the distribution of Cr.
[0033] Figure 6 XPS images of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of this invention are shown below; where: (a) is the full spectrum scan, (b) is the Co2p fine spectrum, (c) is the Mo3d fine spectrum, (d) is the O1s fine spectrum, (e) is the K2p fine spectrum, (f) is the Mn2p fine spectrum, and (g) is the Cr2p fine spectrum.
[0034] Figure 7 The infrared spectrum of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of this invention;
[0035] Figure 8 The image shows the Raman spectrum of the Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) electrode material in Example 4 of this invention.
[0036] Figure 9 The figures show the electrochemical performance of the Mn / Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) electrode materials in Examples 1-5 of this invention; where: (a) is the CV curve at a scan rate of 0.005 V / s; (b) is the CV curve at a scan rate of 0.001 A / cm². 2 (c) is the GCD diagram under current density; (d) is the specific capacitance diagram; (d) is the AC impedance diagram. Detailed Implementation
[0037] The present invention is further described below through specific examples. However, these examples are merely exemplary and are not limited to the scope of protection of the present invention. In the following examples, unless otherwise specified, the reagents, materials, and instruments used are all conventional reagents, materials, and instruments, all of which are commercially available. The reagents involved can also be synthesized by conventional synthetic methods.
[0038] Example 1
[0039] This embodiment prepares Mn / 1%Cr co-doped biomimetic coral-like KCo2(MoO4)2(OH)(H2O) material. The specific preparation steps are as follows:
[0040] The first step is to weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of potassium permanganate, dissolve them in 60 mL of deionized water, and stir magnetically for 30 min at room temperature to completely dissolve the metal salt and obtain a homogeneous metal salt solution.
[0041] In the second step, while continuously stirring, add 3.96 mmol of ammonium heptamolybdate tetrahydrate, 0.04 mmol of potassium dichromate, and 12 mmol of ammonium fluoride sequentially to the above solution. After the addition is complete, continue magnetic stirring for 30 minutes to ensure that all components are fully dissolved and mixed evenly.
[0042] In the third step, the obtained mixed precursor solution was transferred to a 100 mL stainless steel high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). Then, pre-cut nickel foam (1 cm × 1 cm × 0.15 cm) was placed inside as the in-situ growth substrate. After sealing the reactor, it was placed in a constant-temperature drying oven and heated to 140 °C for 8 hours to carry out the hydrothermal reaction. After the reaction was completed, it was allowed to cool naturally to room temperature.
[0043] The fourth step involves collecting the product after the hydrothermal reaction, removing the nickel foam substrate loaded with the active precursor, and purifying it with deionized water. The product is dispersed in deionized water to form a suspension, ultrasonically cleaned for 1 minute, and then filtered. This process of ultrasonication, washing, and filtration is repeated a total of 3 times to remove residual ions and unreacted impurities from the system.
[0044] The fifth step involves placing the cleaned and filtered nickel foam and the product in an oven and drying them at 80°C for 1 hour to remove residual moisture from the sample surface and pores, thus obtaining a dried precursor powder.
[0045] Step 6: Place the dried nickel foam substrate and solid product in a muffle furnace and heat to 300℃ over a 2-hour program, then calcine at 300℃ for 3 hours. After calcine, cool to below 200℃ over a 2-hour program, and then allow to cool naturally to room temperature with the furnace, thus obtaining the Mn / 1%Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material in situ supported on the nickel foam substrate.
[0046] Step 7: Using a platinum electrode as the counter electrode, a mercury oxide electrode as the reference electrode, and the above-mentioned nickel foam with Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material as the working electrode, and a 3 mol / L KOH solution as the electrolyte, assemble the three-electrode system and perform electrochemical performance testing.
[0047] Example 2
[0048] This embodiment prepares Mn / 2%Cr co-doped biomimetic coral-like KCo2(MoO4)2(OH)(H2O) material. The specific preparation steps are as follows:
[0049] The first step is to weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of potassium permanganate, dissolve them in 60 mL of deionized water, and stir magnetically for 30 min at room temperature to completely dissolve the metal salt and obtain a homogeneous metal salt solution.
[0050] In the second step, while continuously stirring, add 3.92 mmol of ammonium heptamolybdate tetrahydrate, 0.08 mmol of potassium dichromate, and 12 mmol of ammonium fluoride sequentially to the above solution. After the addition is complete, continue magnetic stirring for 30 minutes to ensure that all components are fully dissolved and mixed evenly.
[0051] In the third step, the obtained mixed precursor solution was transferred to a 100 mL stainless steel high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). Then, pre-cut nickel foam (1 cm × 1 cm × 0.15 cm) was placed inside as the in-situ growth substrate. After sealing the reactor, it was placed in a constant-temperature drying oven and heated to 140 °C for 8 hours to carry out the hydrothermal reaction. After the reaction was completed, it was allowed to cool naturally to room temperature.
[0052] The fourth step involves collecting the product after the hydrothermal reaction, removing the nickel foam substrate loaded with the active precursor, and purifying it with deionized water. The product is dispersed in deionized water to form a suspension, ultrasonically cleaned for 1 minute, and then filtered. This process of ultrasonication, washing, and filtration is repeated a total of 3 times to remove residual ions and unreacted impurities from the system.
[0053] The fifth step involves placing the cleaned and filtered nickel foam and the product in an oven and drying them at 80°C for 1 hour to remove residual moisture from the sample surface and pores, thus obtaining a dried precursor powder.
[0054] Step 6: Place the dried nickel foam substrate and solid product in a muffle furnace and heat to 300℃ over a 2-hour program, then calcine at 300℃ for 3 hours. After calcine, cool to below 200℃ over a 2-hour program, and then allow to cool naturally to room temperature with the furnace, thus obtaining the Mn / 2%Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material in situ supported on the nickel foam substrate.
[0055] Step 7: Using a platinum electrode as the counter electrode, a mercury oxide electrode as the reference electrode, and the above-mentioned nickel foam with Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material as the working electrode, and a 3 mol / L KOH solution as the electrolyte, assemble the three-electrode system and perform electrochemical performance testing.
[0056] Example 3
[0057] This embodiment prepares Mn / 3%Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) material. The specific preparation steps are as follows:
[0058] The first step is to weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of potassium permanganate, dissolve them in 60 mL of deionized water, and stir magnetically for 30 min at room temperature to completely dissolve the metal salt and obtain a homogeneous metal salt solution.
[0059] In the second step, while continuously stirring, add 3.88 mmol of ammonium heptamolybdate tetrahydrate, 0.12 mmol of potassium dichromate, and 12 mmol of ammonium fluoride sequentially to the above solution. After the addition is complete, continue magnetic stirring for 30 minutes to ensure that all components are fully dissolved and mixed evenly.
[0060] In the third step, the obtained mixed precursor solution was transferred to a 100 mL stainless steel high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). Then, pre-cut nickel foam (1 cm × 1 cm × 0.15 cm) was placed inside as the in-situ growth substrate. After sealing the reactor, it was placed in a constant-temperature drying oven and heated to 140 °C for 8 hours to carry out the hydrothermal reaction. After the reaction was completed, it was allowed to cool naturally to room temperature.
[0061] The fourth step involves collecting the product after the hydrothermal reaction, removing the nickel foam substrate loaded with the active precursor, and purifying it with deionized water. The product is dispersed in deionized water to form a suspension, ultrasonically cleaned for 1 minute, and then filtered. This process of ultrasonication, washing, and filtration is repeated a total of 3 times to remove residual ions and unreacted impurities from the system.
[0062] The fifth step involves placing the cleaned and filtered nickel foam and the product in an oven and drying them at 80°C for 1 hour to remove residual moisture from the sample surface and pores, thus obtaining a dried precursor powder.
[0063] Step 6: The dried nickel foam substrate and solid product are placed in a muffle furnace and heated to 300 °C over a 2-hour time program, and then calcined at 300 °C for 3 hours. After calcination, the temperature is lowered to below 200 °C over a 2-hour time program, and then allowed to cool naturally to room temperature with the furnace, thus obtaining the Mn / 3%Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material in situ supported on the nickel foam substrate.
[0064] Step 7: Using a platinum electrode as the counter electrode, a mercury oxide electrode as the reference electrode, and the above-mentioned nickel foam with Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material as the working electrode, and a 3 mol / L KOH solution as the electrolyte, assemble the three-electrode system and perform electrochemical performance testing.
[0065] Example 4
[0066] This embodiment prepares a Mn / 5%Cr co-doped biomimetic coral-like KCo2(MoO4)2(OH)(H2O) material. The specific preparation steps are as follows:
[0067] The first step is to weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of potassium permanganate, dissolve them in 60 mL of deionized water, and stir magnetically for 30 min at room temperature to completely dissolve the metal salt and obtain a homogeneous metal salt solution.
[0068] In the second step, while continuously stirring, add 3.8 mmol of ammonium heptamolybdate tetrahydrate, 0.2 mmol of potassium dichromate, and 12 mmol of ammonium fluoride sequentially to the above solution. After the addition is complete, continue magnetic stirring for 30 minutes to ensure that all components are fully dissolved and mixed evenly.
[0069] In the third step, the obtained mixed precursor solution was transferred to a 100 mL stainless steel high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). Then, pre-cut nickel foam (1 cm × 1 cm × 0.15 cm) was placed inside as the in-situ growth substrate. After sealing the reactor, it was placed in a constant-temperature drying oven and heated to 140 °C for 8 hours to carry out the hydrothermal reaction. After the reaction was completed, it was allowed to cool naturally to room temperature.
[0070] The fourth step involves collecting the solid product after the hydrothermal reaction, removing the nickel foam substrate loaded with the active precursor, and purifying it with deionized water. The product is dispersed in deionized water to form a suspension, ultrasonically cleaned for 1 minute, and then filtered. This process of ultrasonication, washing, and filtration is repeated a total of 3 times to remove residual ions and unreacted impurities from the system.
[0071] The fifth step involves placing the cleaned and filtered nickel foam and the product in an oven and drying them at 80°C for 1 hour to remove residual moisture from the sample surface and pores, thus obtaining a dried precursor powder.
[0072] Step 6: Place the dried nickel foam substrate and the product in a muffle furnace and heat to 300℃ over a 2-hour program, then calcine at 300℃ for 3 hours. After calcine, cool to below 200℃ over a 2-hour program, and then allow to cool naturally to room temperature with the furnace, thus obtaining the in-situ Mn / 5%Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material supported on the nickel foam substrate.
[0073] Step 7: Using a platinum electrode as the counter electrode, a mercury oxide electrode as the reference electrode, and the above-mentioned nickel foam with Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material as the working electrode, and a 3 mol / L KOH solution as the electrolyte, assemble the three-electrode system and perform electrochemical performance testing.
[0074] To clarify the crystal phase and structural integrity of the Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) material prepared by hydrothermal method, this study characterized the phase of a series of samples by X-ray diffraction. Figure 1 The results showed that the characteristic diffraction peaks of all samples were highly matched with the standard card 04-015-9088, with sharp peaks and high intensity, and no impurity peaks, broadened peaks, or diffuse peaks appeared. This proves that the hydrothermal process successfully synthesized high-purity, high-crystallinity hydroxyl hydrated potassium cobalt molybdate KCo2(MoO4)2(OH)(H2O). The introduction of Mn and Cr ions did not destroy the main framework and crystal form of the parent material, and the material maintained good long-range order and crystal stability.
[0075] The refined results revealed a significant and systematic anisotropic expansion of the cell parameters after doping. The standard sample cell parameters were a = 9.58 Å, b = 6.50 Å, and c = 7.85 Å, while after doping, they precisely evolved to a = 9.74266 Å, b = 6.56870 Å, and c = 7.88342 Å, respectively. The triaxial expansion exhibited significant anisotropy, with the a-axis showing the most dramatic increase at approximately 1.70%, significantly higher than the b-axis (approximately 1.06%) and c-axis (approximately 0.43%). This preferential relaxation behavior along the a-axis can be attributed to the lower atomic packing density and weaker coordination field stabilization energy along this axis, making it easier for foreign substitution ions to induce preferred structural distortion in this direction. This refined change confirms that Mn and Cr ions have substantially dissolved into the lattice by substituting Co sites, and the effective ionic radius of the dopant ions is larger than that of Co. 2+This leads to the elongation of adjacent Co-O bond lengths, thereby inducing overall lattice expansion. Mn and Cr are co-introduced into the lattice during synthesis; both are substituent ions occupying Co sites, with Mn being the dominant dopant and Cr a trace co-doperant. From a function-oriented structural chemistry perspective, this directional lattice expansion induced by Mn / Cr co-doping has a dual positive effect. The crystallographic channel size widened along the a-axis effectively reduces the migration barrier of ions in the interlayer or tunnel structure, which is beneficial to promoting macroscopic ion transport dynamics. Simultaneously, the local lattice distortion induced by Mn substitution can moderately enhance the flexibility of the Co-O-Mo covalent bonds, which is expected to effectively buffer volumetric strain during electrochemical cycling, thereby synergistically improving the cycling durability of the material.
[0076] The intrinsic crystal structure of this material can be analyzed at the atomic scale, such as... Figure 2 As shown, it uses rigid MoO4 tetrahedra and distorted CoO6 octahedra as basic building blocks. The latter is coordinated by lattice oxygen, hydroxyl groups, and coordinated water. The two are connected by sharing vertices and edges to form a stable three-dimensional layered framework. Among them, high-valence Mo 6+ The strong Mo-O covalent bonds act as rigid supports to suppress irreversible framework collapse during charging and discharging, while Co... 2+ The octahedral coordination field exhibits moderate Jahn-Teller distortion activity, capable of absorbing applied stress through local structural relaxation without inducing long-range failure, while the K-channels within the interlayer channels... + Not only does it compensate for negative charges, but its larger ionic radius also pre-supports the interlayer spacing, reserving diffusion paths for subsequent ion migration. After doping, the lattice undergoes anisotropic expansion along the a-axis, where the atomic packing density is lowest. Foreign ions preferentially relax along this direction to release elastic strain. During this process, the bond lengths and bond angles of the MoO4 tetrahedra remain almost undisturbed, while the CoO6 octahedra absorb local strain energy through the non-uniform stretching of the Co-O bonds, thus maintaining their connectivity and long-range order under macroscopic cellular expansion. Therefore, the rigid MoO4 framework provides structural support against volumetric deformation, while the flexible distortion of CoO6 imparts elastic buffering capacity, and K... + The pre-supported interlayer channels construct low-barrier diffusion paths, and the three elements work synergistically and complementaryly in terms of structural stability and ion transport dynamics, laying a solid crystallographic foundation for excellent electrochemical performance from the intrinsic configuration level.
[0077] To visualize the spatial configuration of materials and their morphological response to doping modifications at the microscale, this study systematically characterized the microstructure of KCo2(MoO4)2(OH)(H2O) samples using scanning electron microscopy, such as... Figure 3As shown, the product mainly exhibits a rod-shaped substrate morphology. This rod-shaped structure is formed by layering lamellar morphologies longitudinally, with the layers tightly packed together and minimal gaps. The overall structure is dense and compact, lacking interconnected multi-level pores. The structure is hierarchical and does not form an open three-dimensional network framework, which is not conducive to the rapid penetration of electrolyte and ion transport within the bulk phase. Notably, the outer surface of the rod-shaped particles is coated with a unique biomimetic coral skeleton multi-level framework structure. This coral skeleton shell uses ultrathin two-dimensional nanosheets as basic growth units, and through hydrothermal self-assembly-induced three-dimensional cross-linking and radiation growth, it spontaneously constructs a rigid, hollow, interconnected, and porous three-dimensional open framework. Its hierarchically interconnected pore configuration highly matches the multi-level structure of natural coral skeleton. This coral skeleton shell has a regular morphology, with uniform nanosheet thickness, smooth surface, and clear edges. The interlacing support between the layers forms a large number of interconnected interstitial channels, constructing a stable ion and electron mixed transport network. This multi-level composite configuration organically combines a dense rod-shaped core with a porous coral-like shell. The core provides stable structural support, while the shell endows the material with a high specific surface area and abundant ion channels, providing an ideal geometric substrate for high-density exposure of electrochemical active sites and rapid electrolyte wetting, thereby improving the charge storage performance of supercapacitor electrodes. In summary, the composite configuration with a dense rod-shaped core and a porous coral-like shell combines structural stability with a high active surface area, making it an advantageous morphology for imparting excellent electrochemical performance to the material.
[0078] Figure 4 The image shows the EDS spectrum of the KCo2(MoO4)2(OH)(H2O) material. Peaks for K, Co, Mo, O, Mn, and Cr can be observed in the image. Figure 5 The elemental distribution map shows that when the Mn / Co ratio is approximately 1.0, the oxygen content in this region is 56.33 at%, which is highly consistent with the theoretical stoichiometry of the target crystalline phase, indicating good lattice composition integrity. Moderate Mn substitution only induces localized elastic strain, allowing the nanosheets to retain their anisotropic growth capability and self-assemble into a three-dimensional porous framework. The elemental surface distribution shows that each element exhibits a continuous, uniform, and completely overlapping diffuse distribution within the coral skeleton region, without any anomalies such as local enrichment or component loss, reflecting optimal chemical homogeneity.
[0079] To clarify the elemental composition, chemical valence state, and electronic structure response of the material surface to doping modification, X-ray photoelectron spectroscopy was used to systematically analyze the KCo2(MoO4)2(OH)(H2O) sample. Figure 6 As shown. Figure 6 a is the XPS full scan spectrum of the sample, where the characteristic signals of Co 2p, Mo 3d, O 1s, K 2p, Mn 2p and Cr 2p can be clearly observed, among which the O element has the highest signal intensity.
[0080] Figure 6 b is a high-resolution Co 2p spectrum, which can be decomposed into Co 2p... 3 / 2 With Co 2p 1 / 2 Two sets of spin-orbit splitting characteristic peaks. Co 2p 3 / 2 In the region, the fitted peaks at 780.08 eV and 781.50 eV are attributed to Co, respectively. 3+ With Co 2+ ; corresponding Co 2p 1 / 2 In the region, the characteristic peaks at 795.04 eV and 796.29 eV also correspond to Co. 3+ and Co 2+ Furthermore, typical satellite oscillation peaks of cobalt ions were observed at 785.96 eV, 789.69 eV, 801.81 eV, and 804.60 eV, further confirming the presence of Co in the sample. 2+ The existence of high-valence Mn. 3+ / Mn 4+ and trace amounts of Cr 3+ Replaces low-valence Co in the crystal lattice 2+ At the site, in order to maintain lattice electroneutrality, some Co... 2+ Oxidized to Co 3+ This led to Co 3+ The relative proportion increases. The coexistence of multiple cobalt oxidation states provides abundant redox active sites, which is beneficial for improving the pseudocapacitive performance of the electrode.
[0081] Figure 6 c is the high-resolution Mo 3d XPS spectrum, with 231.71 eV and 234.86 eV corresponding to Mo 3d... 5 / 2 and Mo3d 3 / 2 The spin-orbit splitting energy is 3.15 eV, which is attributed to Mo in the molybdate group. 6+ After doping, Mo mainly retains the +6 valence, with no obvious low-valence molybdenum component appearing, and the 3d peak position of Mo does not shift. This phenomenon clearly indicates that the introduction of dopant ions mainly regulates the electronic state of cobalt sites, while the chemical valence state and coordination environment of the MoO4 tetrahedral rigid unit remain undisturbed.
[0082] Figure 6 d is a high-resolution O 1s spectrum, which can be deconvoluted into three sets of characteristic components. The fitting peak at 529.56 eV is attributed to the metal-oxygen lattice bond in the molybdate framework; the characteristic signal at 530.75 eV corresponds to the hydroxyl group in the crystal structure; and the component at 532.21 eV originates from lattice water and surface adsorbed water molecules.
[0083] Figure 6e is the high-resolution K 2p XPS spectrum, showing two sets of spin-orbit splitting characteristic peaks, with 292.22 eV and 295 eV corresponding to K 2p peaks, respectively. 3 / 2 With K 2p 1 / 2 K, belonging to the interstitial space of the crystal lattice + This confirms that potassium ions were successfully embedded within the crystal structure. The K 2p characteristic peak was fully preserved after doping, indicating that the potassium ion sites in the crystal were not destroyed. However, the high-valence state Mn... 3+ / Mn 4+ Replace Co 2+ After that, interlayer K + The electrostatic attraction between K and the shelf increases, causing K to + The binding energy is slightly increased.
[0084] Figure 6 f is a high-resolution Mn 2p XPS spectrum, showing the Mn 2p... 3 / 2 With Mn 2p 1 / 2 The spin-orbit splitting bimodal pattern, with the fitted components at 642.07 eV and 644.26 eV respectively, is attributed to Mn. 4+ With Mn 3+ 653.75 eV corresponds to Mn 2p 1 / 2 Characteristic peaks. Mn 3+ / Mn 4+ The presence of mixed valence states stems from the partial reduction of potassium permanganate by the reducing agent during the hydrothermal process. Mn does not precipitate as an independent crystalline phase, but exists within the crystal lattice as highly dispersed substituted ions. Figure 6 g is the high-resolution XPS spectrum of Cr 2p, with peaks at 570.15 eV and 571.50 eV attributed to Cr 2p. 3 / 2 , respectively corresponding to Cr 3+ With a small amount of Cr 6+ The value of 572.55 eV belongs to Cr 2p. 1 / 2 Characteristic peaks.
[0085] The functional groups and framework groups of the KCo2(MoO4)2(OH)(H2O) sample were analyzed by Fourier transform infrared spectroscopy, such as... Figure 7 As shown. 538.14 cm -1 The absorption peak at 840.96 cm⁻¹ can be attributed to the coupled bending vibrations of the metal-oxygen bonds in the CoO₆ octahedron and MoO₄ tetrahedron. -1 With 927.76 cm -1The two characteristic absorptions correspond to the stretching vibrations of the Mo-O bonds in the molybdate tetrahedra, confirming the construction of the molybdate inorganic framework. After Mn / Cr co-doping, the Mo-O stretching vibration peaks remained stable, indicating that the bonding environment of the rigid MoO4 tetrahedral units remained undisturbed. (1033.84 cm⁻¹) -1 The absorption peak at 1639.49 cm⁻¹ originates from the bending vibration of the metal-hydroxyl group in the crystal, directly confirming the retention of hydroxyl groups within the structure. -1 The absorption peak at 3348.42 cm⁻¹ is attributed to the HOH bending vibrations of lattice water and surface-adsorbed water molecules. -1 The broad absorption band at 3734.18 cm corresponds to the stretching vibration of the hydroxyl group with the OH group in the lattice water, while 3734.18 cm -1 The sharp peaks at these points correspond to the stretching vibrations of hydroxyl groups on the material surface. These three sets of absorption peaks related to hydroxyl groups and water molecules were all retained after doping, indicating that doping did not lead to the removal of hydroxyl groups and water from the crystal structure, and the material maintained a complete aqueous crystal structure. The presence of lattice water molecules and hydroxyl groups is beneficial for electrolyte wetting and ion transport at the electrode interface, playing a positive role in pseudocapacitive reactions.
[0086] Raman spectroscopy was used to further investigate the lattice vibrations and chemical bond information of the KCo2(MoO4)2(OH)(H2O) sample, such as... Figure 8 As shown. 321.126 cm -1 The peak at 516.093 cm⁻¹ can be attributed to the coupling between the bending vibrations of the molybdate tetrahedron and the bending vibrations of the Co–O lattice; -1 The peak at this point corresponds to the bending vibration of the CoO6 octahedron. 635.601 cm⁻¹ -1 With 727.075 cm -1 The peaks at 858.774, 893.954, and 908.437 cm⁻¹ are attributed to vibrations of Mo–O–Co and Mo–O–Mo bridged oxygen bonds, respectively, proving the existence of a multi-metal-oxygen bridged crosslinking framework in the system. -1 The three peaks at that point represent the stretching vibration mode of the molybdate tetrahedron, and the significant splitting of these peaks indicates that they are influenced by K. + Due to the combined effects of Co doping, hydroxyl groups, and lattice water, localized lattice distortion occurred in the molybdate tetrahedron. (1077.38 cm⁻¹) -1 With 1178.03 cm -1 The peak at 1288.10 cm⁻¹ is attributed to the vibration of hydroxyl groups within the crystal lattice. -1 and 1933.34 cm -1 The signal at this location is attributed to the harmonics and combination frequencies of the framework vibrations. Apart from slight shifts in the positions of some peaks, no characteristic peaks of any new phases were observed, indicating that the substitution of Co sites by dopant ions only induced local lattice distortions and did not disrupt the main framework structure of the molybdate.
[0087] Example 5
[0088] This embodiment prepares a Mn / 7%Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) material. The specific preparation steps are as follows:
[0089] The first step is to weigh 3 mmol of cobalt nitrate hexahydrate and 1 mmol of potassium permanganate, dissolve them in 60 mL of deionized water, and stir magnetically for 30 min at room temperature to completely dissolve the metal salt and obtain a homogeneous metal salt solution.
[0090] In the second step, while continuously stirring, add 3.72 mmol of ammonium heptamolybdate tetrahydrate, 0.28 mmol of potassium dichromate, and 12 mmol of ammonium fluoride sequentially to the above solution. After the addition is complete, continue magnetic stirring for 30 minutes to ensure that all components are fully dissolved and mixed evenly.
[0091] In the third step, the obtained mixed precursor solution was transferred to a 100 mL stainless steel high-pressure hydrothermal reactor lined with polytetrafluoroethylene (PTFE). Then, pre-cut nickel foam (1 cm × 1 cm × 0.15 cm) was placed inside as the in-situ growth substrate. After sealing the reactor, it was placed in a constant-temperature drying oven and heated to 140 °C for 8 hours to carry out the hydrothermal reaction. After the reaction was completed, it was allowed to cool naturally to room temperature.
[0092] The fourth step involves collecting the solid product after the hydrothermal reaction, removing the nickel foam substrate loaded with the active precursor, and purifying it with deionized water. The product is dispersed in deionized water to form a suspension, ultrasonically cleaned for 1 minute, and then filtered. This process of ultrasonication, washing, and filtration is repeated a total of 3 times to remove residual ions and unreacted impurities from the system.
[0093] The fifth step involves placing the cleaned and filtered nickel foam and the product in an oven and drying them at 80°C for 1 hour to remove residual moisture from the sample surface and pores, thus obtaining a dried precursor powder.
[0094] Step 6: Place the dried nickel foam substrate and the product in a muffle furnace and heat to 300℃ over a 2-hour program, then calcine at 300℃ for 3 hours. After calcine, cool to below 200℃ over a 2-hour program, and then allow to cool naturally to room temperature with the furnace, thus obtaining the Mn / 7%Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material in situ supported on the nickel foam substrate.
[0095] Step 7: Using a platinum electrode as the counter electrode, a mercury oxide electrode as the reference electrode, and the above-mentioned nickel foam with Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrode material as the working electrode, and a 3 mol / L KOH solution as the electrolyte, assemble the three-electrode system and perform electrochemical performance testing.
[0096] The electrochemical performance of Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) material grown in situ on nickel foam was tested. Figure 9 (a) Cyclic voltammetry curves of the Mn / Cr co-doped KCo2(MoO4)2(OH)(H2O) electrodes in Examples 1-5 of this invention in the potential range of 0 to 0.5 V. As the Cr doping ratio increases from 1% to 3%, the closed integral area of the CV curve gradually increases; among them, the 3% Cr-doped sample has the largest CV enclosing area and the highest redox peak current. At this doping ratio, moderate Mn substitution induces anisotropic lattice expansion, and the crystallographic channel widened along the a-axis effectively reduces the ion migration barrier. At the same time, Mn... 3+ / Mn 4+ The introduction of mixed valence states increases Co 3+ / Co 2+ The ratio of redox pairs provides a richer pool of charge-compensating active sites.
[0097] Figure 9 (b) The constant current charge-discharge curves of electrodes with different Cr doping in Examples 1-5 of this invention within the potential window of 0 to 0.5 V. The GCD curves of each group of samples show clear charge-discharge voltage plateaus, exhibiting typical pseudocapacitive characteristics. As the Cr doping ratio increases to 3%, the charging time is longer, but the discharge time is less than 5%.
[0098] Figure 9 (c) shows the curves of the areal capacitance of electrodes with different Cr doping in Examples 1-5 of the present invention as a function of current density. At 0.001 A / cm² 2 Under the specified current density, the initial specific capacity of the 5% Cr sample reached a maximum of 18.88 F / cm². The appropriately doped sample exhibited the most sufficient exposure of electrochemical active sites and optimal charge storage capacity at low currents. Further observation revealed that a 7% doping ratio also introduced sufficient active sites. As the current density increased from 0.001 A / cm²... 2 Increased to 0.1 A / cm 2 The specific capacity of the 7%Cr-doped sample remained at a high level, and the decay was the most gradual at high current density. This is due to the greater lattice expansion and interlayer channel widening effect, which significantly optimized the ion diffusion dynamics and enhanced the high current tolerance of the electrode, thus exhibiting a better rate retention capability.
[0099] Figure 9 (d) shows the AC impedance diagrams of electrodes with different Cr doping in Examples 1-5 of this invention. The solution resistance of all samples remained within a narrow range, indicating that the bulk impedance introduced by the current collector and electrolyte was low. The charge transfer resistance of the 3% Cr sample was extremely low, indicating that the charge transfer barrier at the electrode interface was extremely low at this doping ratio, and the redox reaction kinetics were the most superior. The charge transfer resistance of the 5% Cr sample was low, showing good interfacial reactivity. However, the charge transfer resistance of the 7% Cr doped sample was relatively high, indicating that excessive lattice distortion or structural densification increased the energy barrier for interfacial charges to cross the electric double layer.
[0100] Based on the description in the foregoing specification, those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention.
Claims
1. A Mn / Cr co-doped biomimetic coral-bone-like KCo2(MoO4)2(OH)(H2O) supercapacitor electrode material, characterized in that, The electrode material is grown in situ on the surface of a nickel foam substrate. Mn and Cr ions dissolve into the crystal lattice by substituting Co sites, inducing anisotropic lattice expansion. The Mn element is distributed as Mn... 3+ / Mn 4+ Cr exists in mixed valence states, with Cr mainly existing as Cr 3+ The valence state exists, Mo remains at +6, and the bonding environment of the KCo2(MoO4)2(OH)(H2O) matrix is not disrupted.
2. The electrode material according to claim 1, characterized in that, The molar percentage of Cr doping is 1%~7%; when the doping amount is 3%, the electrode has the lowest charge transfer impedance; when the doping amount is 5%, it has an impedance of 0.001 A / cm. 2 At the current density, the electrode area specific capacitance reaches 18.88 F / cm². 2 When the doping concentration is 7%, the electrode exhibits the best rate retention capability.
3. The electrode material according to claim 1, wherein the microstructure comprises a dense rod-shaped core and a three-dimensional biomimetic coral skeleton multi-level porous shell formed by the self-assembly of ultrathin nanosheets.
4. The method for preparing the electrode material according to any one of claims 1 to 3, characterized in that, Includes the following steps: The first step is to dissolve cobalt nitrate hexahydrate and potassium permanganate in deionized water and stir magnetically to obtain a homogeneous metal salt solution. The second step is to add ammonium heptamolybdate tetrahydrate, potassium dichromate and ammonium fluoride in sequence, and continue stirring to obtain a mixed precursor solution; The third step involves transferring the obtained mixed precursor solution into a polytetrafluoroethylene-lined high-pressure reactor, placing nickel foam as an in-situ growth substrate, sealing it, and then carrying out a hydrothermal reaction. After the reaction is completed, the reactor is allowed to cool naturally to room temperature. The active precursor and the nickel foam substrate are then removed, washed, and dried. The fourth step involves placing the dried active precursor and the nickel foam substrate in a muffle furnace for calcination. After calcination, a supercapacitor electrode material with Mn / Cr co-doped biomimetic coral bone-like KCo2(MoO4)2(OH)(H2O) loaded in situ on the nickel foam substrate is obtained.
5. The preparation method according to claim 4, characterized in that, In the first step, the amount of cobalt nitrate hexahydrate added was 3 mmol, the amount of potassium permanganate added was 1 mmol, and the volume of deionized water was 60 mL. In the second step, the amount of ammonium fluoride added was 12 mmol, and the total amount of ammonium heptamolybdate tetrahydrate and potassium dichromate was fixed at 4 mmol. The molar percentage of Cr doping in the system was controlled by adjusting the amount of potassium dichromate added. The cobalt salt and potassium permanganate were first stirred for 30 min to dissolve them. After adding the molybdenum source, chromium source, and ammonium fluoride, the stirring was continued for another 30 min.
6. The preparation method according to claim 4, characterized in that, In the third step, the hydrothermal reactor has a capacity of 100 ml, and the nickel foam has a size of 1 cm × 1 cm × 0.15 cm. The hydrothermal reaction temperature is 140℃, and the holding time is 8 h. The washing process involves washing three times with deionized water. The drying temperature is 80℃, and the drying time is 1 h.
7. The preparation method according to claim 4, characterized in that, In the fourth step, the calcination process involves raising the temperature to 300°C over 2 hours, holding the temperature for 3 hours, and then gradually lowering the temperature to below 200°C over a 2-hour program before cooling the furnace to room temperature.
8. A supercapacitor, characterized in that, The electrode material described in any one of claims 1 to 3 is used as the positive electrode, and the electrolyte is a 3 mol / L KOH alkaline electrolyte.
9. The supercapacitor according to claim 8, characterized in that, The supercapacitor is a three-electrode testing device or an asymmetric supercapacitor device.
10. The application of the KCo2(MoO4)2(OH)(H2O) electrode material according to any one of claims 1 to 3 in portable electronic devices, hybrid vehicles, or smart grid energy storage supercapacitors.